2015
DOI: 10.11646/zootaxa.4013.3.5
|View full text |Cite
|
Sign up to set email alerts
|

A new leech species (Hirudinida: Erpobdellidae: Erpobdella) from a cave in the West Azerbaijan province of Iran

Abstract: Erpobdella borisi n. sp. is a predatory leech inhabiting cave waters in Iran. Probably, it is either a troglobiont or troglophile. The leech has no eyes, and the complete mid-body somite is divided unequally into five annuli. Results of phylogenetic analysis based on morphological characters and COI gene sequence indicate the species to be closely related to Erpobdella japonica, E. octoculata and E. testacea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…(100 mm). Erpobdella borisi, described from a cave in north-west Iran, is also not whitish, but the dorsal surface shows dark pattern and the annulation is Dina-like (Cichocka et al 2015). The somites of D. ratschaensis, D. absoloni and E. borisi are quinqueannulate with the last annulus (b6) broadened.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…(100 mm). Erpobdella borisi, described from a cave in north-west Iran, is also not whitish, but the dorsal surface shows dark pattern and the annulation is Dina-like (Cichocka et al 2015). The somites of D. ratschaensis, D. absoloni and E. borisi are quinqueannulate with the last annulus (b6) broadened.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Erpobdella borisi Cichocka et al, 2015 was first recorded and described from subterranean freshwater habitats in northwestern Iran. Interestingly, the new samples presented herein, unlike the subterranean individuals, possess eyespots and the specimens were collected from super-terranean surface waters in the same region.…”
Section: Dna Barcoding Of Erpobdellidaementioning
confidence: 99%
“…Regarding molecular phylogenetic studies on leeches from Iran, the first analysis was carried out on the piscicolid Pterobdellina arugamensis (de Silva, 1963), from the Persian Gulf by Polgar et al (2009). Further, Cichocka et al (2015) identified a new freshwater subterranean leech, Erpobdella borisi Cichocka & Bielecki, 2015, from northwestern Iran using a DNA barcoding approach. Darabi-Darestani et al (2018) investigated the genetic variation within specimens of the Persian medicinal leech, Hirudo orientalis Utevsky & Trontelj, 2005, from Iran and neighboring regions.…”
mentioning
confidence: 99%
“…We know of only 43 obligate groundwater species from Iran, despite the fact that 10.5% of the country (compared with approximately 1.7% of Europe) is underlain by carbonate rock formations. The obligate groundwater fauna includes four fish species, 23 amphipods of the genus Niphargus Schiødte, 1847, 12 copepods, one oligochaete, one gastropod and two isopods (Cichocka et al 2015;Mousavi-Sabet et al 2016;Malek-Hosseini and Zamani 2017;Vatandoust et al 2019;Bargrizaneh et al 2021;Malek-Hosseini et al 2021). The only two obligate groundwater isopods known from Iran are Microcharon raffaellae Pesce, 1979 (Lepidocharontidae) collected from a well in Pliocenic sandstone and clay at Shahr-e-Kord city, Chaharmahal and Bakhtiari Province, and Stenasellus tashanicus Khalaji-Pirbalouty, Fatemi, Malek-Hosseini & Kuntner, 2018 (Stenasellidae) collected from Tashan karstic cave in Khuzestan province (Pesce 1979;Khalaji-Pirbalouty et al 2018).…”
Section: Introductionmentioning
confidence: 99%